Identifying technical, physiological, tactical and psychological characteristics that contribute to career progression in soccer - Forsman, H.; Blomqvist, M.; Davids, K.; Liukkonen, J.; Konttinen, N. (International Journal of Sports Science & Coaching, 2016)
This study sought to examine which technical, physiological, tactical and psychological characteristics at age 15 years contribute to successful soccer performance at age 19 years. Participants were male soccer players (n=114; mean age 15.4±0.3 years), divided into elite and sub-elite groups based on their performance level at age 19 years. Technical, physiological, tactical and psychological characteristics were recorded when players were 15-year olds. Binary logistic regression analysis showed that performance level at age 19 was clearly associated with technical skills of passing and centering as well as agility and motivation levels recorded at age 15 years. These results extend our understanding of career progression in youth soccer and highlight the multidimensional nature of talent development processes in soccer. Moreover, it seems crucial that coaching support should be devoted to the development of passing and centering skills, agility and motivation in the development of youth players. ABSTRACT FROM AUTHOR